PELAKSANAAN PEMBELAJARAN DARING DAN LURING DENGAN METODE BIMBINGAN BERKELANJUTAN PADA GURU SEKOLAH DASAR DI TELUK BETUNG UTARA BANDAR LAMPUNG - Malyana, Andasia (LPPM STKIP PGRI Bandar Lampung, 2020)
The problem raised in the study was the low competence of teachers in implementing online and offline learning according to standard processes during the Covid-19 outbreak. Meanwhile, one of the teacher's duties is to carry out meaningful learning in order to achieve maximum learning objectives. The purpose of this study was to improve competence in implementing online and offline learning through guidance with the consultation method for elementary school teachers in Teluk Betung Utara Bandar Lampung in 2020. The results showed that in cycle I teacher competence reached a score of 37 or reached 52% and cycle II reached a score of 68 or reaching 95%, which is increasing from cycle I to cycle II and achieving indicators of research success. Based on the results of this study, it is concluded that the competence of implementing online and offline learning can be improved through guidance with the consultation method for elementary school teachers in Teluk Betung Utara, Bandar Lampung.